Tujuan dan Urgensi Studi Islam dalam Konteks Keilmuan: The Purpose and Urgency of Islamic Studies in a Scientific Context - Romat Efendi Sipahutar; Umi Kalsum; Devi syukri Azhari (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Islamic studies play a crucial role in establishing a scientific foundation that emphasizes not only intellectual aspects but also the moral and spiritual development of humankind. This research is motivated by the need to re-understand the essence of Islamic studies as a discipline capable of contributing to the development of modern science without losing Islamic values. In the context of globalization and technological advancement, the urgency of Islamic studies is increasingly prominent, as it can serve as an ethical and spiritual foundation for the development of civilized science. This research employs a descriptive qualitative approach, with a literature review as the primary method. Data were collected through an analysis of various scientific literature, journals, and academic works relevant to the theme of integrating Islamic science and values. An in-depth analysis was conducted to identify the relationship between the objectives of Islamic studies and their contributions to the development of science and the character formation of Muslim scientists. The results show that Islamic studies serve as a means of integrating religious and general sciences, emphasizing a balance between rationality and spirituality. This study also contributes to the development of a scientific paradigm oriented toward human welfare and moral sustainability. In conclusion, Islamic studies have strategic urgency in the context of modern science because they can guide its development so that it remains grounded in the values of monotheism, justice, and humanity.